Aktivitas Antibakteri Isolat Jamur Endofit Kulit Batang Rimbang (Solanum torvum Swartz) terhadap Beberapa Bakteri - Melzi Octaviani; Salsabila Putri; Sri Lidya Rasihe; Kolista Sisilawati; Nofriyanti Nofriyanti; Rahmayati Rusnedy (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Endophytic fungi are known as a promising alternative source of antibacterials due to their ability to synthesize secondary metabolites like their host plants. Although the presence of endophytic fungi associated with Solanum torvum has been reported in previous studies, no studies have focused on fungi isolated from the bark of Solanum torvum and the correlation between the phytochemical content of its fractions and antibacterial activity. The aim of this study was to isolate endophytic fungi from the bark of Solanum torvum and test the antibacterial activity and phytochemical profiles of the fractions from the isolates against pathogenic bacteria. Endophytic fungi were isolated using direct cultivation techniques after surface sterilization. The antibacterial activity test was evaluated using the disc diffusion method against Bacillus cereus ATCC 11778, Staphylococcus aureus ATCC 12600, Escherichia coli ATCC 11775, and Salmonella typhi ATCC 14028 bacteria. Five endophytic fungal isolates were obtained and identified, namely FEST-K1 (Artrographis), FEST-K2 (Acremonium sp.), FEST-K3 (Paecilomyces sp.), FEST-K4 (Lichtheimia), and FEST-K5 (Alternaria sp.). The supernatant was then extracted and fractionated using ethyl acetate, chloroform, and n-butanol. Phytochemical analysis showed that the fungal fraction contained alkaloids, terpenoids, and saponins. FEST-K1 showed the strongest inhibitory activity against S. aureus and B. cereus, with inhibition zone diameters of 15.09 mm and 13.69 mm, respectively. In contrast, the highest activity against E. coli and S. typhi was observed in FEST-K4 (13.78 mm) and FEST-K5 (15.45 mm). One-way ANOVA statistical analysis showed that the antibacterial activity of the fungal extracts was significantly different from the positive control (p < 0.05). These results indicate that endophytic fungi derived from the bark of S. torvum are a potential source of antibacterial compounds.